Sustainable Education Through Information and Communication Technology: A Case Study on Enhancing Digital Competence and Academic Performance of Social Science Higher Education Students - Milkova, Eva; Moldoveanu, Mirela; Krcil, Tomas (Sustainability, 2025)
Background: Developing young people’s technical and Information and Communication Technology skills is an SDG 4 target (4.4.), while the use of online educational material is a promoted tool to implement SDGs-related measures. Methodology: This is a case study exploring the complex role of ICT in teaching social sciences at a higher education institution using quantitative and qualitative research methods. Employing Urie Bronfenbrenner’s ecological systems theory, the research investigates how digital tools impact students’ academic performance across three courses with varying levels of ICT integration. The study evaluates students’ digital skills, compares the effectiveness of ICT-based and traditional teaching methods, and analyses how these methods influence the students’ comprehension and performance of the subject matter. Results: The findings revealed that while certain ICT skills and competencies enhance students’ academic performance, students value ICT tools differently depending on the course’s subject matter and their own digital competencies. The research also highlights the importance of teachers’ ability to blend ICT and non-ICT activities effectively to enhance students’ understanding. Conclusions: The study contributes to the ongoing discourse on ICT in education, emphasising the need for a more nuanced, multi-layered approach to understanding the intersection between technology and education, particularly in non-technical fields like social sciences.